Comparison of Novel Oral Anticoagulants and Vitamin K Antagonists in Patients With Cerebral Venous Sinus Thrombosis on Efficacy and Safety: A Systematic Review - Li, Hongjie; Yao, Meiling; Liao, Songjie; Chen, Jingyan; Yu, Jian (Frontiers in Neurology, 2020)
Vitamin K Antagonists (VKAs) are guideline suggested subacute anticoagulants for cerebral venous sinus thrombosis (CVST). However, the bleeding events limit their wide use in clinical practice. In the last decade, novel oral anticoagulants (NOACs) have been applied as an alternative to VKAs in some kinds of thromboembolic diseases, with a reduction of bleeding events. Whether NOACs could replace VKAs in CVST treatment remains unclear. We conducted a comparison between the two types of medicines on efficacy and safety for the treatment of CVST based on the present clinical evidence from a literature search. The results suggested that there is no statistical difference between the two types of medicines on efficacy and safety. In conclusion, the application of NOACs for CVST is noninferior to that of VKAs in terms of efficacy and safety.